Gender Equality in Families in Kerinci - Prasetia, Agung; Harmalis, Harmalis; Firman, Firman; Afdal, Afdal (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
This study is being done in Kerinci to find out how people understand and interpret gender and how the five Kerinci men and women are being used as informants based on life guidance, social relationships, perceptions of patriarchy, social behavior, and the woman's dual role. Case studies and phenomenological data are used in this qualitative study. The informants are chosen on purpose. There are five Kerinci men and women with more than one job, such as government workers, business owners, politicians, or people who run home businesses. The results of this study show that in five cases of Kerinci man and wife informants understand and interpret gender as agreement and conformity of man's and woman's function in taking the role based on cultural and religious values, which are Hargo lihi, adat istiadat, raso sgan, raso go, and religiosity, as part of life-guidance, because these values become the binding frame of man and wife in gender implementation. In the five Kerinci man and wife as informants’ case, the double roles of women are seen in the financial development, spiritual gift, motivation, and achievement of themselves and their family. This is because Kerinci people don't stop their wives from working, and their religion lets them do so as long as they keep their hargo lihi, self-esteem, and husband's agreement. Even though there isn't much time to spend at home with your husband in the evening, that doesn't mean it's not good.